2022
DOI: 10.3389/fdata.2022.871236
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Views on Sharing Digital Data for Public Health Surveillance: Analysis of Survey Data Among Patients

Abstract: Digital data, including social media, wearable device data, electronic health records, and internet search data, are increasingly being integrated into public health research and policy. Because of the current issues around public distrust of science and other ethical issues in public health research, it is essential that researchers conduct ongoing studies assessing people's perceptions around and willingness to share digital data. This study aims to examine participants' social media use and comfort sharing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Three studies reported that data type determines one's willingness to share, and one of them observed that participants were in favour of sharing “traditional” health data as opposed to social media and device/app data. 64 Other insights provided by these studies suggest that people categorized as belonging to the pandemic cohort were more comfortable with sharing their PHID compared with those belonging to the pre-pandemic cohort, 65 and that privacy-preserving techniques can play an important role in someone's willingness to share. 66 , 67 …”
Section: Resultsmentioning
confidence: 98%
“…Three studies reported that data type determines one's willingness to share, and one of them observed that participants were in favour of sharing “traditional” health data as opposed to social media and device/app data. 64 Other insights provided by these studies suggest that people categorized as belonging to the pandemic cohort were more comfortable with sharing their PHID compared with those belonging to the pre-pandemic cohort, 65 and that privacy-preserving techniques can play an important role in someone's willingness to share. 66 , 67 …”
Section: Resultsmentioning
confidence: 98%
“…The COVID-19 pandemic has aroused debate concerning PHI. Public health authorities recognized the need to carry out contact-tracing and personal restrictions, which entailed collecting and sharing personal data and PHI (e.g., personal localization, results of SARS-CoV-2 tests) through and between public organizations ( 17 , 33 , 34 ). Consequently, the management of PHI during the pandemic raised serious privacy concerns ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…A direct consequence of health digitalization is the availability of a variety of data, many of which can be considered personal data concerning health or personal health information (PHI) ( 15 ). Such complex and rich data may drive the development of high-performing big data and artificial intelligence (AI) systems in health care, which are also fundamental in producing new insights for clinical research ( 16 , 17 ). For this reason, digital health and health-data management have become a priority, firmly embedded in EU policy and funding goals ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the nature of the research focus plays a crucial role. Human studies are typically subject to stricter ethical guidelines and consent requirements, and data sharing regulations [22][23][24] . These regulations may limit the extent of metadata that can be collected, whereas non-human studies may not encounter the same constraints 22,[24][25][26] .…”
Section: Discussionmentioning
confidence: 99%